Building it better: Applying human–computer interaction and persuasive system design principles to a monetary limit tool improves responsible gambling - Wohl, Michael J.A.; Parush, Avi; Kim, Hyoun (Andrew) S.; Warren, Kristen (Computers in human behavior, 2014)
•Responsible gambling tools have not been created with the end-user in mind.•A new RG tool was created using HCI and PSD principles (Study 1).•Responsible gambling improved with the new HCI and PSD-inspired tool (Study 2).•Findings have implications for building effective responsible gambling tools. In two studies, we aimed to improve the responsible gambling (RG) utility of monetary limit tools for non-disordered Electronic Gambling Machine (EGM) players – the target population for such prevention-oriented RG tools. To this end, based on feedback from focus groups with non-disordered EGM players, we created a new monetary limit tool that incorporated EGM players’ desired functionality coupled with design fundamentals of Human Computer Interaction (HCI) and Persuasive Systems Design (PSD; Study 1). We then tested the newly created HCI and PSD inspired tool and compared its RG utility (limit adherence) against a standard monetary limit tool (Study 2). Non-disordered EGM players were randomly assigned to experience the HCI and PSD inspired or the standard monetary tool prior to gambling in a virtual realty casino. As predicted, participants adhered to their pre-set monetary limits more (92%), when exposed to the HCI and PSD inspired pop-up tool than the standard monetary limit tool (62.2%). Improving RG tools through the use of HCI and PSD principles is discussed.